Ethical considerations for human–animal neurological chimera research: mouse models and beyond. (10th October 2019) - Hyun, Insoo
Abstract : Research that uses stem cell‐based chimeras promises to advance our understanding of human developmental biology, as well as new medical interventions, such as generating transplantable human organs in livestock. However, along with these exciting research possibilities come moral concerns about the moral humanization of animals, especially when it comes to the potential effects of human cells in the brains of experimental animals. Recent work involving neurologically chimeric mice may suggest that such worries are reasonable. However, this overlooks the crucial social and neurological conditions for enabling the development of conscious self‐awareness, the absence of which leaves us only with animal welfare to monitor and consider. Abstract : This commentary discusses moral concerns and implications of current efforts to generate human chimerism in the brain of experimental animals, offering practicable considerations to guide research.